Evaluation for energy efficiency for Green Building Index: case study for UITM test cell / Amirah Hashifudin - Hashifudin, Amirah (2010)
Energy efficiency and indoor environment quality are among the assessment criteria for Green Building Index for Malaysia. In this study, a test cell building is used as a case study to evaluate the heat transfer through window and the OTTV of building and also the daylighting. Data of the surface temperature and indoor air temperature were recorded using automated data logger at an interval of 10min for duration of three days. The indoor and the outdoor illuminance were recorded using hand held lux meter. Data were processed for the conductive heat transfer through window and the daylight factor for two window types named clear float and tinted. Result shows that the installation of tinted film on window is reduce the indoor air temperature and daylight factor by 6.8% and 7.82% respectively. The daylight factor of clear float window is 8.1% and tinted windows are 0.28%. The OTTV value of clear float and tinted window also reduce from 18.83W/m2 to 10.56W/m2. The energy used for cooling load can be reduces by installation of tinted film to window. Unfortunately, the energy consumption of the building will used to light up the space since the building with tinted windows has low illuminance level.